Two inborn errors of metabolism in a newborn: glutaric aciduria type I combined with isobutyrylglycinuria - Popek, Manuela; Walter, Melanie; Fernando, Malkanthi; Lindner, Martin; Schwab, Karl Otfried; Sass, Jörn Oliver (Clinica chimica acta, 2010)
Background - Glutaric aciduria type 1 (GA1) is an inborn error in the metabolism of the amino acids tryptophan, lysine and hydroxylysine due to mutations in the GCDH gene coding for glutaryl-CoA dehydrogenase. Affected individuals often suffer from an encephalopathic crisis in infancy or childhood which results in acute striatal injury leading to a severe dystonic-dyskinetic movement disorder. Isobutyryl-coenzyme dehydrogenase (IBD) is an enzyme encoded by the ACAD8 gene and involved in the catabolism of the branched-chain amino acid valine. Both GA1 and IBD deficiency can be detected by expanded newborn screening using tandem-mass spectrometry, if they are considered screening targets. - Methods - Tandem-mass spectrometry and gas-chromatography with mass-selective detection were used for the assessment of key metabolites in body fluids of a patient with abnormal findings in newborn screening. Mutations were investigated by direct sequencing and by restriction fragment lengths analysis. Valine metabolism was studied in vitro in immortalized lymphocytes. - Results - Following accumulation of acylcarnitines C5DC and C4, of 3-hydroxyglutaric acid and isobutyrylglycine in body fluids, sequence analysis in the GCDH gene revealed homozygosity for a missense mutation in exon 6, c.482G>A, p.Arg161Gln, which had been reported in GA1 before. In the ACAD8 gene a novel mutation c.841+3G>C was identified, which results in loss of exon 7 and predicts a premature stop of translation. Impaired valine degradation was corroborated by the increased post-load level of acylcarnitine C4 in lymphocytes. - Conclusion - The molecular basis of two inborn errors of metabolism in a newborm was elucidated. The metabolite studies underline the use of urinary C4 acylcarnitine as a sensitive marker of IBD deficiency. A functional test of IBD activity in lymphocytes may replace more invasive fibroblast studies. In view of the combination of two organic acidurias, which may both affect the level of free carnitine, careful follow-up including regular assessment of the carnitine status of the patient appears prudent.
Gesehen am 05.05.2023